HBR guide to building your business case - Sheen, Raymond; Gallo, Amy. (Boston, Massachusetts : Harvard Business Review Press, 2015)
"You've got a great idea that will increase revenue or productivity-but how do you get approval to make it happen? By building a business case that clearly shows its value. Maybe you struggle to win support for projects because you're not sure what kind of data your stakeholders will trust, or naysayers always seem to shoot your ideas down at the last minute. Or perhaps you're intimidated by analysis and number crunching, so you just take a stab at estimating costs and benefits, with little confidence in your accuracy. To get any idea off the ground at your company you'll have to make a strong case for it. This guide gives you the tools to do that"--
"You've got a great idea that will increase revenue or productivity--but how do you get approval to make it happen? By building a business case that clearly shows its value. Maybe you struggle to win support for projects because you're not sure what kind of data your stakeholders will trust, or naysayers always seem to shoot your ideas down at the last minute. Or perhaps you're intimidated by analysis and number crunching, so you just take a stab at estimating costs and benefits, with little confidence in your accuracy. To get any idea off the ground at your company you'll have to make a strong case for it. This guide gives you the tools to do that"--
Keywords: Business planning; New business enterprises -- Planning; Strategic planning; BUSINESS & ECONOMICS / Business Communication / Meetings & Presentations; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Strategic Planning; Print books